Reproducción humana asistida, consideraciones jurídicas y bioéticas, límites y alcances - Bailón Cabrera, José de Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
The legal research regarding Assisted Human Reproduction implies the use of many legal concepts related to the social sciences. This document provides the reader with schedules of peculiar innovative contents pertaining to the application of modern Biotechnology to the human needs and the solutions to such needs, as science evolves. The Assisted Human Reproduction as it relates to the Law, shall propose a scientific universe of that which is desirable, by introducing Bioethics, as a new science of specific spectrum, which may provide responses by applying both Genetics and Medicine to the ethical perspective. Bioethics shall oblige the decision maker to undertake a profound analysis of the subjects that are implied in each of the techniques that are used in order to attain a specific result. The mere presence of such techniques, prove the presence of an almost infinite number of legal schedules, that must be tested against their teleological pertinence. Juridical responses must be then provided to such ethical analysis, and the Law must provide legal institutions and solutions that provide adequate responses to the dynamics that science requires. The discoveries of scientists provide the questions that then, the Law must provide adequate responses to, as a social science. The Human Genome, Nanotechnology, and other related concepts, oblige the Law to provide the analysis and the responses that are adequate and ethical in every case. It is for such reason that Bioethics are the proper and adequate space to provide ideas, principles and legal innovative argumentation. The purpose of the evolution of the techniques of Assisted Human Reproduction is and shall be to satisfy human needs, and therefore, must reject mere whims (including those of a scientific nature) and the production of genetic garbage. It must be able to attain procreation of the human being, consistent with the authentic principles and values that justify such scientific endeavor.

La Investigación Jurídica de la Reproducción Humana Asistida provoca el empleo de múltiples posturas conceptuales típicas de las ciencias sociales, que ofertarán esquemas de contenidos peculiares de escenarios de cosas nuevas por la aplicación de una Biotecnología moderna atenta a las necesidades humanas que impliquen satisfactores en la medida que las ciencias evolucionen. La Reproducción Humana Asistida acompañada del Derecho propondrá un universo científico enunciativamente deseable. Hace entrar en el espectro singular, a otra ciencia nueva llamada Bioética, que informará en consecuencia lo que es propio por la Genética y la Medicina, ya que nos obligará a la reflexión profunda de lo que implica cada una de las técnicas que se practican para lograr su cometido. La sola presencia de dichas técnicas, dan cuenta de una derrama infinita de esquemas jurídicos donde precisamente su pertinencia teleológica será punto del desarrollo propio del Derecho, que implicará atender instituciones jurídicas ya establecidas, que habrán de ser sometidas a la dinámica que la ciencia va logrando. Los descubrimientos científicos dan pauta a que el mismo Derecho haga lo suyo como ciencia social. El Genoma Humano, la Nanotecnología, etcétera dan pie a la reflexión antes dicha, muy cuidadosa, por el mismo Derecho, por eso la Bioética nos da el espacio propio y adecuado para proponer las ideas, los principios y argumentos de lo que el propio Derecho aborda con la ciencia nueva. El propósito de la evolución de las Técnicas de Reproducción Humana es y será satisfacer necesidades humanas, no caprichos, menos científicos, como tampoco lo es la producción de basura genética, sino una procreación del ser humano cargada de valores y principios auténticos que justifique es esfuerzo científico. La creación del ser humano es entonces un valor universal.
Facultad de Derecho y Ciencias Sociales. Doctorado interinstitucional en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-D-2015-1451; Consideraciones; Limites; Alcances; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/888